A high temperature electret material and preparation method thereof
Through the preparation and power-up electret technology of high-temperature electret materials, the problem of insufficient performance of existing electret materials at high temperatures is solved, and high-temperature stability and strong electret capability are achieved. It is suitable for the use of waste gas removal from multiple pollution sources. .
Patent Information
- Application Number
- CN201910683215.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-07-26
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2039-07-26
AI Technical Summary
Due to poor temperature resistance, existing electret materials limit their application fields and application ranges, and cannot be used for a long time and continuously at high temperatures, resulting in insufficient electret capability.
Using high-temperature electret material, by mixing metal element powder with metal compounds, heating decomposition and hot pressing to form inorganic or organic compounds with energy level defects, lattice defects, and structural defects, and adding them in combination with corona Electric electret improves the high temperature stability and electret capability of the material.
The electret material has been used for a long-term and continuous period at high temperatures above 300°C, which significantly improves the electret capability and is suitable for a wide range of pollution-source waste gas fields, including the removal of solid particulate matter and aerosols.
Smart Images

Figure HDA0002145404220000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection, and relates to a high-temperature electret material and a preparation method thereof, which are used for improving the working temperature range and electret capacity of the existing electret material. Background Art
[0002] Academically, electret material research has a long history and there are many theories. However, in practical applications, the application scope and application field of electret materials are still relatively narrow. Only a few products such as electret headphones and electret masks are common, and their electret capabilities are relatively general. The main reason is that most of the common electret materials currently use organic materials such as polymers or plastics as electret materials. Polymer materials are basically not heat-resistant. At high temperatures, the electret material itself will undergo lattice rearrangement and even molecular bond breaking, decomposition, oxidation and combustion, which destroys the electret properties of the electret itself.
[0003] The reason why the electret material has the electret property is mainly due to the defects formed in the preparation and processing process such as crystallization and molding, such as energy level defects, lattice defects and structural defects, or the combination and superposition of the above defects.
[0004] The electret material can be completely separated from the power supply and independently provide an electric field to form an electric field force. Since it is separated from the power supply, the shortcomings of the power supply itself are eliminated, and a continuous and stable electric field can be formed without interruption. At the same time, it has great convenience and freedom in the use process. It has a wide range of use value and great market value.
[0005] At present, the electret materials, which are mainly organic materials, are basically developed based on polymer materials such as PP and PE, and their temperature resistance is poor. On the one hand, their application fields and scope are limited; on the other hand, their preparation methods and electrification (electret) methods are also limited. Therefore, the existing electret materials cannot be widely used due to their self-high temperature performance limitations. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a high-temperature stable and high-electret material to significantly improve the normal working temperature and electret capacity of the electret material, thereby greatly improving the field and scope of promotion and use of the electret material.
[0007] To achieve the above-mentioned purpose and other related purposes, the first aspect of the present invention provides a high-temperature electret material, which is an inorganic compound and / or organic compound having the ability to form an electret property, wherein the inorganic compound and / or organic compound includes two or more defects among energy level defects, lattice defects, and structural defects.
[0008] Preferably, the normal operating temperature of the high temperature electret material is ≥300° C. More preferably, the normal operating temperature of the high temperature electret material is ≥500° C.
[0009] Preferably, the inorganic compound is selected from one or more combinations of oxygen-containing compounds, nitrogen-containing compounds or glass fibers.
[0010] More preferably, the oxygen-containing compound is selected from one of metal-based oxides, oxygen-containing complexes or oxygen-containing inorganic heteropolyacid salts.
[0011] Further preferably, the metal-based oxide is selected from one or more combinations of aluminum oxide, zinc oxide, zirconium oxide, titanium oxide, barium oxide, tantalum oxide, silicon oxide, lead oxide, and tin oxide.
[0012] Most preferably, the metal-based oxide is aluminum oxide.
[0013] Further preferably, the oxygen-containing composite is selected from one or more combinations of titanium-zirconium composite oxides or titanium-barium composite oxides.
[0014] Further preferably, the oxygen-containing inorganic heteropoly acid salt is selected from one or more combinations of zirconium titanate, lead zirconate titanate or barium titanate.
[0015] More preferably, the nitrogen-containing compound is silicon nitride.
[0016] Preferably, the organic compound is selected from one or more combinations of fluoropolymers, polycarbonates, PP, PE, PVC, natural waxes, resins, and rosins.
[0017] More preferably, the fluoropolymer is selected from one or more combinations of polytetrafluoroethylene (PTFE), polyperfluoroethylene-propylene (Teflon-FEP), soluble polytetrafluoroethylene (PFA), and polyvinylidene fluoride (PVDF).
[0018] Most preferably, the fluoropolymer is polytetrafluoroethylene (PTFE).
[0019] Preferably, the inorganic compound and / or organic compound having two or more defects among energy level defects, lattice defects, and structural defects accounts for ≤10% of the total mass percentage of the compound. More preferably, the inorganic compound and / or organic compound having two or more defects among energy level defects, lattice defects, and structural defects accounts for ≤1% of the total mass percentage of the compound.
[0020] The second aspect of the present invention provides a method for preparing a high-temperature electret material, which comprises mixing a metal element powder with a metal compound, and then treating and molding the mixture to obtain the desired electret material.
[0021] Preferably, the metal element is selected from one or more combinations of aluminum, zinc, zirconium, titanium, barium, tantalum, silicon, lead and tin.
[0022] Preferably, the particle size of the metal element powder is 100-1000 mesh.
[0023] Preferably, the purity of the metal element is ≥ 99.9 wt %. More preferably, the purity of the metal element is ≥ 99.99 wt %.
[0024] Preferably, the metal compound is an inorganic acid salt or an organic acid salt of the above metal elements.
[0025] More preferably, the inorganic acid salt is a nitrate or a carbonate.
[0026] More preferably, the organic acid salt is oxalate.
[0027] Preferably, the mass ratio of the metal element powder to the metal compound is 100:1-20. More preferably, the mass ratio of the metal element powder to the metal compound is 100:5-15.
[0028] Preferably, the mixing is a chemical precipitation method or a vapor deposition method.
[0029] Preferably, the treatment is thermal decomposition.
[0030] Preferably, the forming is performed in a mold, and the material of the mold is diamond.
[0031] Preferably, the forming is hot pressing forming, the temperature of the hot pressing forming is 500-600° C.; the pressure of the hot pressing forming is 3-7 atmospheres; and the time of the hot pressing forming is 30-90 minutes.
[0032] The third aspect of the present invention provides a post-processing method for a high-temperature electret material, which comprises fine-machining the electret material prepared as above, wherein the machining accuracy of the fine-machining is controlled to be ≤0.5 microns.
[0033] More preferably, the finishing accuracy is controlled to be ≤0.1 micron.
[0034] A fourth aspect of the present invention provides a method for electret charging of a high-temperature electret material, wherein the electret material after post-treatment is used as an electrode for electret charging.
[0035] Preferably, the electrode is a positive electrode or a negative electrode.
[0036] More preferably, the electrode is a positive electrode.
[0037] Preferably, the electret charging is performed by corona method, in which the electrostatic field voltage is 100,000-200,000 volts.
[0038] A fifth aspect of the present invention provides a use of a high-temperature electret material in removing particulate matter from exhaust gas emitted by a pollution source.
[0039] Preferably, the pollution source is a mobile pollution source or a fixed pollution source.
[0040] More preferably, the mobile pollution source is selected from one of a vehicle or a ship.
[0041] Further preferably, the mobile pollution source is selected from one of a vehicle engine or a ship engine.
[0042] Further preferably, the vehicle is selected from one of a motor vehicle or a locomotive.
[0043] More preferably, the stationary pollution source is a facility that emits industrial waste gas.
[0044] As described above, the present invention provides a high-temperature electret material and a preparation method thereof, and there is no similar technical solution. The prepared high-temperature electret material can be used normally, for a long time, and continuously at 300°C or higher, and has excellent high-temperature electret performance. The electrostatic adsorption device prepared with it as the core device can be widely used in various waste gas fields from various pollution sources, and can remove various solid particles, aerosols and even liquid particles in the waste gas. The preparation method of this high-temperature electret material is simple, the preparation cost is low, and it can be prepared using existing common preparation steps. The high-temperature electret material obtained by the present invention has a wide range of optional processing, detection and characterization methods, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a basic schematic diagram of a method for preparing a high-temperature electret material in the present invention. DETAILED DESCRIPTION
[0046] The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention.
[0047] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0048] The first aspect of the present invention provides a high-temperature electret material, which is an inorganic compound and / or organic compound having the ability to form an electret property, wherein the inorganic compound and / or organic compound includes but is not limited to having two or more defects among energy level defects, lattice defects, and structural defects.
[0049] In the present invention, the electret material refers to a material with electret capability. The electret capability refers to the ability of the electret material to carry an electric charge after being charged by an external power source, and to still maintain a certain charge when completely disconnected from the power source, thereby functioning as an electrode in an electrostatic field.
[0050] In the high temperature electret material provided by the present invention, the high temperature electret material refers to an electret material with a normal working temperature higher than 300° C. Furthermore, the normal working temperature of the high temperature electret material is higher than 500° C.
[0051] The energy level defect refers to the transition energy level of molecules or atoms in the compound and the electronic transition during the transition, and there are unknown uncertain defects. In the high temperature electret material provided by the present invention, the compound with energy level defects is, for example, zirconium oxide with Schottky defect structure.
[0052] The crystal defect refers to the defect that the crystal structure of the compound has both amorphous and crystalline structures regardless of its crystal structure. Wherein, the crystal structure is selected from one of a low-temperature stable crystal structure, a high-temperature stable crystal structure, an intermediate crystal structure or an amorphous structure. In the high-temperature electret material provided by the present invention, the crystal defect is the doping of an amorphous structure in the crystalline structure of the crystal structure bulk phase. Specifically, a compound with crystal defects, such as gama crystal-type aluminum oxide, also has a bulk phase doped with a small amount of beta-, data-, or even an amorphous structure.
[0053] The structural defects refer to defects such as pores and bubbles in the material during the molding process due to the influence of external factors (such as temperature, pressure, atmosphere, etc.). In the high-temperature electret material provided by the present invention, the structural defects include but are not limited to porous structural defects. Specifically, a compound with structural defects such as a specific surface area of 300m 2 / g or more gama crystal porous alumina.
[0054] In the high-temperature electret material provided by the present invention, the inorganic compound can be an oxygen-containing compound. As a compound containing oxygen, the oxygen-containing compound can generally be a metal-based oxide, and the metal-based oxide can specifically be, for example, aluminum oxide, zinc oxide, zirconium oxide, titanium oxide, barium oxide, tantalum oxide, silicon oxide, lead oxide, tin oxide, etc. It can also be other oxygen-containing complexes that maintain structural stability at high temperatures such as 300°C, preferably above 500°C, specifically titanium zirconium composite oxide or titanium barium composite oxide, or it can be an oxygen-containing inorganic heteropoly acid salt, specifically zirconium titanate, lead zirconate titanate (PZT), barium titanate. The inorganic compound can also be a nitrogen-containing compound, and the nitrogen-containing compound can be silicon nitride. The inorganic compound can also be glass fiber. The best inorganic compound can be aluminum oxide.
[0055] In the high-temperature electret material provided by the present invention, the organic compound can be fluoropolymer, polycarbonate, PP, PE, PVC, natural wax, resin, rosin, etc.
[0056] Specifically, the fluoropolymer may be polytetrafluoroethylene (PTFE), polyperfluoroethylene propylene (Teflon-FEP), soluble polytetrafluoroethylene (PFA), polyvinylidene fluoride (PVDF), etc. The best organic compound may be polytetrafluoroethylene (PTFE).
[0057] In the high-temperature electret material provided by the present invention, the inorganic compound and / or organic compound having two or more defects among energy level defects, lattice defects, and structural defects accounts for ≤10% of the total mass percentage of the compound. Preferably, the inorganic compound and / or organic compound having two or more defects among energy level defects, lattice defects, and structural defects accounts for ≤1% of the total mass percentage of the compound.
[0058] The second aspect of the present invention provides a method for preparing a high-temperature electret material, which comprises mixing a metal element powder with a metal compound, and then treating and molding the mixture to obtain the desired electret material.
[0059] In the preparation method of the high temperature electret material provided by the present invention, the metal element is selected from one or more combinations of aluminum, zinc, zirconium, titanium, barium, tantalum, silicon, lead, tin, etc. The oxide, nitride or other compound form of the metal element has two or more defects among energy level defects, lattice defects and structural defects, which can form electret properties.
[0060] In the preparation method of the high temperature electret material provided by the present invention, the particle size of the metal element powder is selected according to actual needs. However, relatively speaking, the particle size of the metal element powder is preferably in the range of 100-1000 mesh, and can be 100-400 mesh, 200-600 mesh, 500-800 mesh, 400-1000 mesh, and preferably 400 mesh.
[0061] In the preparation method of the high temperature electret material provided by the present invention, the metal element is required to maintain high purity, and the purity is selected according to actual needs. However, relatively speaking, the preferred purity is ≥99.9wt%, preferably ≥99.99wt%.
[0062] In the preparation method of the high temperature electret material provided by the present invention, the metal compound is an inorganic acid salt or an organic acid salt of the above metal element. The metal compound is easily decomposed by heating. The inorganic acid salt can specifically be a nitrate such as aluminum nitrate or zirconium nitrate, a carbonate, etc. The organic acid salt can specifically be an oxalate.
[0063] In the preparation method of the high temperature electret material provided by the present invention, the metal compound is required to maintain high purity, and the purity is selected according to actual needs. However, relatively speaking, the preferred impurity content is ≤0.5wt‰, preferably ≤0.1wt‰.
[0064] In the method for preparing the high-temperature electret material provided by the present invention, the mass ratio of the metal element powder to the metal compound is 100:1-20. Usually, the mass ratio of the two added is more preferably 100:5-15.
[0065] In the preparation method of the high temperature electret material provided by the present invention, the mixing of the metal element powder and the metal compound can be achieved by chemical precipitation method, vapor deposition method, etc. The metal element powder and the metal compound are mixed uniformly.
[0066] In the preparation method of the high temperature electret material provided by the present invention, the treatment is to obtain a compound having electret ability such as an oxygen-containing compound by a chemical method such as heating and decomposing the mixed metal element powder and metal compound.
[0067] In the preparation method of the high-temperature electret material provided by the present invention, the molding is carried out in a mold, the material of the mold is diamond, and the mold is a mold that has been cleaned.
[0068] In the preparation method of the high-temperature electret material provided by the present invention, the forming is hot pressing forming, the temperature of the hot pressing forming is 500-600°C, which can be 500-550°C, 550-600°C, 530-570°C, and preferably 550°C; the pressure of the hot pressing forming is 3-7 atmospheres, which can be 3-5 atmospheres, 5-7 atmospheres, 4-6 atmospheres, and preferably 5 atmospheres; the time of the hot pressing forming is 30-90 minutes, which can be 30-60 minutes, 60-90 minutes, 45-75 minutes, and preferably 60 minutes.
[0069] The third aspect of the present invention provides a post-processing method for a high-temperature electret material, which comprises fine-processing the electret material prepared as above.
[0070] In the post-processing method of the high-temperature electret material provided by the present invention, the finishing process is grinding, and the grinding process is performed on a high-precision grinder. Specifically, the grinding process needs to control the accuracy to ≤0.5 microns, preferably ≤0.1 microns.
[0071] A fourth aspect of the present invention provides a method for electret charging of a high-temperature electret material, wherein the electret material after post-treatment is used as an electrode for electret charging.
[0072] In the electret charging method for high temperature electret material provided by the present invention, the electrode can be a positive electrode or a negative electrode, but relatively speaking, the electrode is preferably a positive electrode.
[0073] In the method for electret charging of high temperature electret material provided by the present invention, the electret charging is performed by corona method. In the corona method, the electrostatic field voltage is selected as required. However, relatively speaking, the preferred electrostatic field voltage is 100,000-200,000 volts, which can be 100,000-150,000 volts, 150,000-200,000 volts, 130,000-170,000 volts, and preferably 150,000 volts.
[0074] In the electrification method for high-temperature electret material provided by the present invention, the electret material can be tested for energy level defects, lattice defects or structural defects before electrification, and the electret ability of the electret material before electrification can be tested simultaneously. The energy level defects, lattice defects or structural defects are tested by atomic energy spectrum, transmission electron microscope or XRD. The electret ability is tested by potentiometer.
[0075] In the method for electret charging of high temperature electret material provided by the present invention, the charge condition of the surface and the body of the electret material can be detected after electret charging to obtain the electret ability of the electret material after electret charging. The charge condition detection is performed by using a potentiometer.
[0076] A fifth aspect of the present invention provides a use of a high-temperature electret material in removing particulate matter from exhaust gas emitted by a pollution source.
[0077] In the use provided by the present invention, the pollution source is a mobile pollution source or a fixed pollution source. The mobile pollution source can be a vehicle, which can be a motor vehicle or a locomotive, and the specific location is the vehicle engine. The mobile pollution source can also be a ship, and the specific location is the ship engine. The fixed pollution source is a facility that emits industrial waste gas.
[0078] Example 1
[0079] Take 100g of 400-mesh gama crystalline aluminum powder with a purity of ≥99.99%, and 10g of aluminum nitrate with an impurity content of ≤0.1‰, mix them evenly by chemical precipitation, and then produce aluminum oxide with electret ability by heating and decomposition. Pour it into a clean diamond mold, and perform hot pressing at 550°C and 5 atmospheres for 60 minutes to obtain the desired electret material sample 1#. The electret material sample 1# is tested by atomic energy spectrum, transmission electron microscopy, and XRD, and it is found that the electret material sample 1# has 0.5% of gama crystalline aluminum oxide with structural defects and crystal defects, and has a surface area of 300m 2 / g or more porous structure, the bulk phase is also doped with a small amount of bata-, data-, or even an amorphous structure.
[0080] The electret material sample 1# was finely processed on a high-precision grinder to achieve a processing accuracy of ≤0.1 micron. The post-treated electret material sample 1# was used as the positive electrode and was electrified (electret) in a 150,000 volt electrostatic field in a corona manner. The electret capacity of the electret material sample 1# before electrification was measured using a potentiometer, and its electret capacity was 1kV / cm 2 .
[0081] After electret charging, at a working temperature of 500°C, a potentiometer was used to detect the charge on the surface and inside of the electret material sample 1#, and the electret capacity of the electret material sample 1# after electret charging was measured. The electret capacity was 3kV / cm 2 The electret material sample 1# was used to prepare the electrode. After electret charging, the electret capacity was continuously tested by electric field. Its electret capacity can maintain 3kV / cm 2 .
[0082] It can be found that after electret charging, the electret ability of electret material sample 1# is greatly improved, from 1kV / cm 2 Increase to 3kV / cm 2, which can effectively remove all kinds of solid particles, aerosols and even liquid particles in the exhaust gas. Electret material sample 1# can be used normally, for a long time and continuously at a working temperature of 500℃, and has good high-temperature electret performance. See the specific process Figure 1 .
[0083] Example 2
[0084] Take 100g of 500-mesh gama crystalline zinc powder with a purity of ≥99.99%, and 15g of zinc carbonate with an impurity content of ≤0.1‰, mix them evenly by vapor deposition, and then generate zinc oxide with electret ability by heating and decomposition. Pour it into a clean diamond mold, and perform hot pressing at 580°C and 4 atmospheres for 70 minutes to obtain the desired electret material sample 2#. The electret material sample 2# is tested by atomic energy spectrum, transmission electron microscopy, and XRD, and it is found that the electret material sample 2# has 1% of gama crystalline zinc oxide with structural defects and energy level defects, which has a surface area of 300m 2 / g or more porous structure and has a Schottky defect structure.
[0085] The electret material sample 2# was finely processed on a high-precision grinder to achieve a processing accuracy of ≤0.1 micron. The post-treated electret material sample 1# was used as the positive electrode and was electrified (electret) in a corona manner under the action of an electrostatic field of 170,000 volts. The electret capacity of the electret material sample 2# before electrification was measured using a potentiometer.
[0086] After electret charging, a potentiometer was used to detect the charge on the surface and inside of electret material sample 2# at a working temperature of 400°C, and it was determined that the electret capacity of electret material sample 2# after electret charging was greatly improved compared with that before electret charging. Electrodes were prepared from electret material sample 2#, and the electret capacity was continuously detected through an electric field after electret charging. Its electret capacity can remain basically unchanged for a long time.
[0087] It can be found that after electret charging, the electret material sample 2# has a greatly improved electret ability, which can effectively remove various solid particles, aerosols and even liquid particles in the exhaust gas. Electret material sample 2# can be used normally, for a long time and continuously at a working temperature of 400℃, and has good high-temperature electret performance. See the specific process for details. Figure 1 .
[0088] Example 3
[0089] Take 100g of 300-mesh gama crystal barium powder with a purity of ≥99.99%, and 5g of barium oxalate with an impurity content of ≤0.1‰, mix them evenly by chemical precipitation, and then produce barium oxide with electret ability by heating and decomposition. Pour it into a clean diamond mold, and perform hot pressing at 530°C and 6 atmospheres for 50 minutes to obtain the desired electret material sample 3#. The electret material sample 3# is tested by atomic energy spectrum, transmission electron microscopy, and XRD, and it is found that the electret material sample 3# has 0.8% of gama crystal barium oxide containing structural defects, crystal defects, and energy level defects, and has a surface area of 300m 2 / g or more porous structure, the bulk phase is also doped with a small amount of bata-, data-, or even an amorphous structure, and has a Schottky defect structure.
[0090] The electret material sample 3# was finely processed on a high-precision grinder to achieve a processing accuracy of ≤0.1 micron. The post-treated electret material sample 3# was used as a positive electrode and was electrified (electret) in a corona manner under the action of an electrostatic field of 130,000 volts. A potentiometer was used to measure the electret capacity of the electret material sample 3# before electrification.
[0091] After electret charging, a potentiometer was used to detect the charge on the surface and inside of electret material sample 3# at a working temperature of 600°C, and it was determined that the electret capacity of electret material sample 3# after electret charging was greatly improved compared with that before electret charging. Electrodes were prepared from electret material sample 3#, and the electret capacity was continuously detected through an electric field after electret charging. Its electret capacity can remain basically unchanged for a long time.
[0092] It can be found that after electret charging, the electret material sample 3# has a greatly improved electret ability, which can effectively remove various solid particles, aerosols and even liquid particles in the exhaust gas. Electret material sample 3# can be used normally, for a long time and continuously at a working temperature of 600℃, and has good high-temperature electret performance. See the specific process for details. Figure 1 .
[0093] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing an electret material, characterized in that: The electret material is an inorganic compound with electret properties, and the inorganic compound includes two or more defects among energy level defects, lattice defects, and structural defects. The preparation method is to mix metal element powder with metal compound, post-process and shape, so as to obtain the required electret material, wherein the metal element is selected from one or more combinations of aluminum, zinc, zirconium, titanium, barium, tantalum, silicon, lead, and tin; the metal compound is an inorganic acid salt or an organic acid salt of the above metal element, and the mass ratio of the metal element powder to the metal compound is 100:1-20. The shaping is hot pressing shaping, and the temperature of the hot pressing shaping is 500-600°C; the pressure of the hot pressing shaping is 3-7 atmospheres; and the time of the hot pressing shaping is 30-90 minutes.
2. The method for preparing an electret material according to claim 1, characterized in that: The mass percentage of the inorganic compound having two or more defects among energy level defects, lattice defects and structural defects in the total compound is ≤10%.
3. A post-processing method for an electret material, comprising: performing fine processing on the electret material prepared by the method for preparing an electret material according to any one of claims 1 to 2, wherein the processing accuracy of the fine processing is controlled to be ≤ 0.5 microns.
4. A method for electret charging of an electret material, comprising using the electret material that has been post-treated by the post-treatment method of the electret material according to claim 3 as an electrode for electret charging.
